Analisis Pembelajaran IPA Menggunakan Pendekatan Lesson Study Learning Melalui Model Transcript Based Learning Analysis (TBLA) Di MTs ABU AMR Tambakrejo Pasuruan - Nikmatul Ulfah; Zulfa Mazida Rohmah; Agus Qowiyuddin (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2024)
Lesson study builds a learning community among teachers, learners, academics and education observers. Transcript Based Learning Analysis (TBLA) model is one of the models used to analyze learning transcripts in more depth. This research aims to describe the lesson study learning pattern in science learning through TBLA analysis. The method used in this research is descriptive qualitative research method to describe the phenomena that take place as it is. The research was conducted in class VIII A MTs ABU AMR Tambakrejo, human respiratory system material, with a cycle of plan, do, see. This research instrument is a video and audio recorder and a researcher's field note sheet. Data collection is done through 3 ways, namely documentation, observation and discussion. The data collected in this research is in the form of transcripts of Lesson study Learning Community learning.The data analysis technique uses TBLA analysis model. The results of the study describe the conversations that occur between teachers and students, linear patterned learning, the category leads to Student Center Learning. The conclusion of this research is that science learning of human digestive system material has a linear pattern that describes learning getting stronger to achieve learning goals and SCL categories that are student-centered. This research suggestion can be used as a reference for reflection in developing teacher professionalism to shape more effective learning.